ANALISIS SATIRE DAN SARKASME DALAM DEBAT CAPRES 2019 DAN IMPLEMENTASINYA TERHADAP PEMBELAJARAN DI SMA - Siti Farmida; Ediwarman, Ediwarman; Tisnasari , Sundawati (Universitas Wiralodra, 2021)
The study discuss the sarcasm and satiric speech in the 2019 presidential candidates debate and the implementations of learning in high school. The purpose of the study are (1) to describe the form of the language style of the sarcasm and the satire in the 2019 presidential candidates debate, (2) to know the use propose the language style of the sarcasm and satire in the 2019 presidential candidates debate. The method used in this research is observation technique and writing technique. The data is this research is sarcasm and satiric speech in the 2019 presidential candidates debate. Based on the result of the research, there are 78 data, 30 data consist of satire speech from expressive speech acts there is 23 data, that is criticism (9), refusal (4), rebuke (1), feel objected (1), to clarifiy (5), complaint (1), quip (1), support (1). The use purpose to satire speech from directive speech acts there is 7 data, that is appeal (3), warning (1), advice (2), to expect (1). The use purpose of sarcasm speech from expressive speech acts there is 47 data, that is accusation (7), quip (12), criticism (11), suspects (2), warning (2), censure (2), blaming (4), deny (2), underestimate (1), pride oneself (1), anger (1), disagree (1), rebuke (1). The use purpose of arcasm speech from directive speech acts there is 1 data, that is advice (1). Keywords: Satire, sarcasm, illocutinary speech acts, the 2019 presidential candidates debate.